Logbook written by a drifter - Mwanaka, Tendai R. (Book collections on Project MUSE., 2018)
Logbook written by a drifter, is a cycle of interlinked poems that deal with life, spirituality, language, philosophy, love and relationships. A main theme are relationships which have changed the character. Those which the character doesn't know how to deal with; which have make the character into a wreck, emotionally, psychologically, or spiritually: he is in a small space. This collection encourages us to keep those spaces, spaces of the drift, until we have faced our challenges, afterall sometimes drifting is all we can do!